Research on linear magnetic reciprocating yarn-guiding system based on axiomatic design. (28th September 2020) - Zhang, Zhiming; Chen, Boya; Lu, Binbin; Lai, Zilong
As a novel product design method, axiomatic design provides momentous theoretical and practical significance in engineering design, quality engineering, and complexity science fields. Based on the axiomatic design and TRIZ theory, this paper proposes the research of the reciprocating yarn-guiding system. First, the function-structure mapping is established by the Z-shaped rule of axiomatic design, then the original design matrix is formed. The independent axiom analyses the original matrix and verifies its coupling. It also was used to analyse the coupling elements, and the 'rotating motor and ball screw' reciprocating yarn guide system was proposed. Then, in order to improve the defects of the 'rotary motor and ball screw' reciprocating yarn-guiding system, we put forward the scheme of a magnetic reciprocating yarn-guiding system. Finally, the motion of the linear magnetic reciprocating yarn-guiding system was simulated by ADAMS software simulation, which verified the feasibility of the system.